Compressive Behavior of Inconel 625 and Ti-6Al-4V Strut Lattices Fabricated by LPBF - Mihaela Raluca Condruz; Teodor Adrian Badea; Alexandru Paraschiv (Applied Sciences)
The present study assessed the compression performance of four strut lattices manufactured via laser powder bed fusion (LPBF), namely selective laser melting (SLM) from Inconel 625 and Ti-6Al-4V. Static finite element analysis and mechanical testing were performed, and it was concluded that the experimentally determined performance trend was in good agreement with that obtained by numerical methods. The cell type greatly influences the compressive performance of the lattices, regardless of the material used for manufacturing. The best compressive performances were recorded for the octet lattice, followed by the truncated octahedron, Kelvin, and re-entrant lattices. Regarding material performance, for the first maximum compressive strength, similar results were recorded for both materials; a difference was recorded in the case of yield strength, with higher values were recorded for Ti-6Al-4V compared to Inconel 625. The average first maximum compressive strength for the Ti-6Al-4V lattice was between 30.39 and 290.17 MPa, and it was within a range of 16.22–258.71 MPa for Inconel 625. The elastic modulus was between 1.74 and 4.72 GPa for Ti-6Al-4V, and 1.13 and 4.46 GPa for Inconel 625. A more ductile behavior was registered for the nickel-based superalloy than for the titanium alloy; the Inconel 625 specimens were characterized by a bending-dominant damage mode, and Ti-6Al-4V specimens were characterized more by a stretch-dominant damage mode.